The impact of knowledge flows on asset specificity from the perspective of open innovation. Issue 3 (16th July 2021) - Zheng, Feihu; Jiao, Hao; Gu, Junyi; Moon, Hwy-Chang; Yin, Wenyan
Abstract : Purpose: This study aims to examine how different modes of knowledge flows affect the changes of asset specificity and how ownership control moderates the relationship between knowledge flows and asset specificity in the open innovation paradigm. Design/methodology/approach: This paper selects information technology outsourcing as the research base. It uses the feasible weighted least squares modeling method for its analysis and has collected the data from 2, 369 research and development contracts of multinational vendor firms in China. Findings: The coupled and outbound knowledge flows have a direct and positive effect on asset specificity. Moreover, the results show that weak corporate control has significant moderating effects on the relationship between both coupled and outbound knowledge flows and asset specificity; the strong control positively moderates the relationship between outbound knowledge flows and asset specificity. Practical implications: In open innovation, firms build a higher degree of asset specificity to maximize the efficiency of knowledge flows, which then helps them to enhance innovation capacity and market performance. Originality/value: Preceding studies have tended to examine the influences of asset specificity as an independent variable in a closed innovation paradigm. Asset specificity is hence often left as the antecedent "black box." This paper, however, opens the "black box" of asset specificity, which is set as a dependent variable, by investigating the influences of knowledge flows on the asset specificity in the context of open innovation. It also reinterprets the role of asset specificity by adopting the lens of open innovation theory.